حقوق ومسؤوليات الولي والوصي والمولى عليهم في قانون الأسرة الأفغاني: دراسة تحليلية قانونية: The Rights and Responsibilities of the Guardian, Custodian, and the Wards in Afghan Family Law: A Legal Analytical Study - Poya, Aminullah; Ghalia, Bouhedda; Bin Awang Hamat, Mohd Afandi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول هذا البحث حقوق ومسؤوليات الأولياء والمولى عليهم وفق قانون الأسرة الأفغاني، عبر تحليل التشريعات ذات الصلة. تهدف الدراسة إلى توضيح العلاقة القانونية بين الأولياء والأوصياء للأشخاص تحت حمايتهم، مع التركيز على بيان الوسائل القانونية المتاحة والالتزامات المتعلقة بالرعاية لضمان حماية حقوق القُصّر والمولى عليهم، والحد من الانتهاكات المحتملة عبر آليات وقائية فعالة. كما تقدم الدراسة تحليلاً للإجراءات القانونية التي تحقق التوازن بين حقوق الأولياء ومسؤولياتهم لضمان مصلحة القُصّر والمولى عليهم وفق القانون الأفغاني مع الإشارة إلى القصور في بنود التشريعات القانونية الحالية. يعتمد هذا البحث على المنهج الكيفي استقراءً وتحليلاً لتأصيل وضبط مفهوم حقوق ومسؤوليات الأولياء والأوصياء والمولى عليهم في ضوء أطر التشريعات القانونية الحالية. تؤكد نتائج البحث على الأهمية البالغة لفهم حقوق ومسؤوليات الولي والوصي والمولى عليهم على مستوياتها الشخصية والمالية والقانونية، مع التركيز على تطويرها وتعزيزها من خلال تشريع بنود قانونية شاملة تواكب المتطلبات المعاصرة. وتكشف الدراسة أنّ المولى عليهم بعد فك الحجر عنهم، يستحق الاستقلال القانوني؛ ورفع القيود على التصرفات المالية؛ والاستقلال في القرارات الشخصية؛ وتحمل كامل المسؤولية القانونية. تقدم هذه الورقة البحثية مجموعة من المقترحات و هي تحديث وتطوير التشريعات القائمة؛ وإنشاء هيئات رقابية مستقلة؛ وتعزيز الوعي المجتمعي وأهمية تمكين المولى عليهم بما يحقق مصلحتهم الشخصية والمالية. ABSTRACT This study examines the rights and responsibilities of guardians and wards under Afghan family law through an analysis of relevant legislation. The research aims to clarify the legal relationship between guardians, custodians, and those under their care, focusing on the legal mechanisms available and the obligations related to guardianship to ensure the protection of minors and legally dependent individuals. It also seeks to mitigate potential violations through effective preventive measures. Furthermore, the study analyzes the legal procedures that balance the rights and responsibilities of guardians to safeguard the best interests of minors and wards in accordance with Afghan law, highlighting shortcomings in the current legal provisions. This research employs a qualitative approach, utilizing both inductive and analytical methods to conceptualize and refine the understanding of the rights and responsibilities of guardians, custodians, and wards in light of existing legal frameworks. The findings underscore the critical importance of comprehending the personal, financial, and legal dimensions of guardianship, with an emphasis on developing and enhancing these aspects through comprehensive legal provisions that align with contemporary needs. The study reveals that once legal incapacitation is lifted, the ward is entitled to legal independence, unrestricted financial decision-making, personal autonomy, and full legal responsibility. Based on these findings, the paper proposes several recommendations, including the modernization and development of existing legislation, the establishment of independent regulatory bodies, and the promotion of public awareness on the significance of empowering wards to secure their personal and financial well-being.